Nonpeptide neurotrophic agents useful in the treatment of neurodegenerative diseases such as Alzheimer's disease - Masaaki Akagi; Nobuaki Matsui; Haruka Akae; Nana Hirashima; Nobuyuki Fukuishi; Yoshiyasu Fukuyama; Reiko Akagi (Elsevier, 2015)
Developed regions, including Japan, have become "aged societies," and the number of adults with senile dementias, such as Alzheimer's disease (AD), Parkinson's disease, and Huntington's disease, has also increased in such regions. Neurotrophins (NTs) may play a role in the treatment of AD because endogenous neurotrophic factors (NFs) prevent neuronal death. However, peptidyl compounds have been unable to cross the blood-brain barrier in clinical studies. Thus, small molecules, which can mimic the functions of NFs, might be promising alternatives for the treatment of neurodegenerative diseases. Natural products, such as or nutraceuticals or those used in traditional medicine, can potentially be used to develop new therapeutic agents against neurodegenerative diseases. In this review, we introduced the neurotrophic activities of polyphenols honokiol and magnolol, which are the main constituents of Magnolia obovata Thunb, and methanol extracts from Zingiber purpureum (BANGLE), which may have potential therapeutic applications in various neurodegenerative disorders.